A preliminary model of iron fertilisation by baleen whales and Antarctic krill in the Southern Ocean: Sensitivity of primary productivity estimates to parameter uncertainty - Ratnarajah, Lavenia; Melbourne-Thomas, Jessica; Marzloff, Martin P.; Lannuzel, Delphine; Meiners, Klaus M.; Chever, Fanny; Nicol, Stephen; Bowie, Andrew R. (Ecological Modelling, 2016)
International audience Large marine animals may play a crucial role in storing and recycling bioavailable iron in surface waters by consuming iron-rich prey and subsequent defecation of iron that is excess to their requirements. This biological recycling of iron could enhance primary productivity in iron-limited waters. However, quantifying the effects of marine animals on ocean primary productivity remains challenging because of a limited understanding of the key biogeochemical processes involved. In this paper, we develop a preliminary model that explores these uncertainties and examines the potential effects of historical populations of blue, fin and humpback whales, and the biomass of Antarctic krill required to support the whale populations, on primary productivity in the Southern Ocean.ăăOur results suggest that, despite conservative estimates for key processes in our model, pre-exploitation populations of blue whales and, to a lesser extent fin and humpback whales, could have contributed to iron recycling, resulting in enhanced phytoplankton production in iron-limited Southern Ocean waters. Iron-rich defecation by un-exploited whale populations in the Southern Ocean, and the biomass Antarctic krill required to support them, could have resulted in a contribution to primary productivity of between 1.5 × 10−4 to 23.4 g C m−2 yr−1 (blue whales), 1.4 × 10−4 to 13.9 g C m−2 yr−1 (fin whales), and 2.4 × 10−5 to 1.7 g C m−2 yr−1 (humpback whales). However, only when all parameter estimates are at their upper limits does there appear to be this significant role for whales in enhancing primary productivity, and thus we need to assess the likelihood of these values arising.ăăThe high degree of uncertainty around the magnitude of these increases in primary productivity is mainly due to our limited quantitative understanding of key biogeochemical processes. To reduce uncertainty regarding the effect of whales on Southern Ocean primary productivity, future research will need to refine our understanding of five ...